ANTHROPOMORPHISM IN THE OLDER BEEKEEPING TERMINOLOGY (Philological Studies, 2019)
The article presents the older beekeeping terminology, which was created in the context of semantic formation modes on the basis of anthropomorphization of bees. In this respect, metaphorical semantic transfer and extension of meaning are demonstrated as the central formation modes, being the only ones to enable cross-domain meaning transfer. The analysis, which was based on four beekeeping works from the period before the formation of unitary standard Slovenian in the middle of the 19th century, revealed that such beekeeping terminology was fairly equally represented in all authors involved, and consequently also in both two provincial versions of the Slovenian language. However, compared to the modern state we have found out that only about a quarter of these terms are preserved in modern beekeeping terminology.
Keywords: older beekeeping terminology, metaphor, extension of meaning